The Influence of Financial Leverage to the Profitability of the Selected Manufacturing Firms Within Metro Manila - De Guzman Judith Anne D.; Castillo, Joan Paul D.; Corsame, Blessy Marie L.; Cruz, Jason Anthony M.; Deniega, Kendrex S.; De Guzman, Ma. Cristina, Eustaquio, Kamille Joy Z.; Faustino, Melvina Criscelle B.; Frias, Richer Grace C.; Gagui. Kolyn M. and Pablo, Carla Me S. 4 0 16; 5
u
Research Paper: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2